Aflatoxin Contamination of Various Staple Foods from Angola and Mozambique - Cláudio Matusse; Zelda Lucamba; João Bila; Custódia Macuamule; Ana Sampaio; Sandra Afonso; Armando Venâncio; Paula Rodrigues (Toxins)
Aflatoxins constitute a significant risk in staple foods produced in African countries. This research aimed to analyze the total aflatoxin (AFT) contamination of various staple foods in Angola and Mozambique. A total of 233 samples of corn, peanuts, beans, rice, and cassava flour collected from farmers or local markets from the province of Cuanza Sul, Angola, and the provinces of Gaza and Inhambane, South Mozambique, were analyzed for the presence of AFT using the lateral flow strip method via AgraStrip® Pro WATEX® (Romer). The results showed that, from all matrices, the highest incidence and level of AFT were found in corn produced in Mozambique, with medians ranging from 6.5 to 66.5 µg/kg, with the samples showing values as high as 9200 µg/kg. Levels higher than the maximum admissible levels recommended by the Codex Alimentarius Commission for cereals and pulses (15 µg/kg) were observed in up to 90% of the corn samples, depending on the province. Corn produced in Angola showed lower amounts of AFT, with medians ranging from 1.2 to 7.7 µg/kg. Considering the maximum admissible levels for AFT recommended by the European Commission and the Codex Alimentarius Commission for cereals and pulses, the level of AFT contamination in staple food produced and consumed in the studied provinces is high and constitutes a public health risk for the population. Therefore, risk mitigation strategies are urgently needed.